Bemerkungen zum Papyrus Moskau 314 - Quack, Joachim Friedrich (Zeitschrift für ägyptische Sprache und Altertumskunde, 2018)
A recent re-publication of the so-called Hymns to the Diadem (pMoscow 314) is an occasion to take up some questions related to that manuscript. It is shown that the original dating to the 17th (or very early 18th) dynasty is correct against the new proposal to date it to the reign of Amenemhet III, and that synchronically the beneficiary of the ritual is a god, even if it is likely to be an adaption of a royal ritual. Linguistic details point towards a date for the composition in the Old Kingdom. Several philological problems are discussed, and weaknesses in the new edition are pointed out.